Investigation of non-volatile additives on the process of distillation of hydrocarbon mixtures - Степанов, М.Б.; Ледовських, В.М.; Дрогобицька, І.В.; Василькевич, О.І. (Proceedings of National Aviation University (archive), 2009)
The given results of researches of influence of nonvolatile additives on processes of distillation of individual hydrocarbons and their mixes, including petroleum and mineral oil. With the help of the developed computer system of the continuous control of distillation it is shown, that at the presence of small amounts of the additive decrease of temperature of the beginning of boiling of hydrocarbons is observed, their speeds of banish and exits of light fuel mineral oil grow during initial oil refining